Quercetagetin alleviates zearalenone-induced liver injury in rabbits through Keap1/Nrf2/ARE signaling pathway - Wu, Fengyang; Wang, Fengxia; Tang, Zhaohong; Yang, Xinyu; Liu, Yanhua; Zhao, Man; Liu, Shudong; Han, Shuaijuan; Zhang, Zhisheng; Chen, Baojiang (Frontiers in Pharmacology, 2023)
Introduction: This study aimed to assess the alleviative effect of quercetagetin (QG) on zearalenone (ZEN)-induced liver injury in rabbits. Methods: Ninety 41-day-old healthy Hyla rabbits were randomly assigned into three groups, including a control (fed with basic diet), ZEN addition group (fed with basic diet + 600 μg/kg ZEN), and ZEN + QG addition group (fed with basic diet + 600 μg/kg ZEN + 100 mg/kg QG), with 30 rabbits per group. The duration of the experiment was 28 days. Results: The results revealed no significant differences in the average daily gain, average daily feed intake, the gain to feed ratio and the liver, kidney and spleen organ indexes (p > 0.05) between the rabbits across the three groups. However, the sacculus rotundus index of the rabbits in the control group was significantly higher than that in the ZEN + QG group (p < 0.05). The intake of ZEN-contaminated diet also significantly increased the activities or levels of alanine transaminase, alkaline phosphatase, total bile acid (TBA), total bilirubin, malondialdehyde, and interleukin-4 (IL-4) and enhanced the abundance of kelch-like ECH-associated protein 1 (Keap1), heat shock protein 70 (HSP70) and cysteine-aspartic acid protease-3 (Caspase-3) mRNA in the blood or liver tissue in ZEN group, compared to the control group (p < 0.05). On the contrary, the activities or levels of immunoglobulin A, complement 3, total antioxidant capacity, glutathione peroxidase (GSH-Px), superoxide dismutase, interleukin-10, and the abundance of nuclear factor E2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) mRNA were significantly decreased (p < 0.05). Supplementing the diet with QG still maintained significantly higher levels of TBA and IL-4, and the abundance of GSH-Px, HSP70, IL-4, and Caspase-3 mRNA in the blood and liver of rabbits in the ZEN + QG group than in the control group (p < 0.05). At the same time, the other indicators were restored to levels in the control group (p > 0.05). Discussion: In conclusion, QG alleviated the ZEN-induced oxidative damage and liver injury caused by inflammatory reaction through the Keap1-Nrf2-antioxidant response element (ARE) signal pathway, which protected the liver. This study revealed the alleviative effect of QG on the hepatotoxicity of ZEN in rabbits for the first time, providing a new perspective for applying QG and developing a ZEN antidote.